Clinical Characteristics and Outcome of Cardiovascular Implantable Electronic Device Infections in Turkey. (July 2016) - Aydin, Mesut; Yildiz, Abdulkadir; Kaya, Zeynettin; Kaya, Zekeriya; Basarir, Ahmet Ozgur; Cakmak, Nazmiye; Donmez, Ibrahim; Morrad, Baktash; Avci, Ahmet; Demir, Kenan; Cagliyan, Emre Caglar; Yuksel, Murat; et al.
Infection is one of the most devastating outcomes of cardiovascular implantable electronic device (CIED) implantation and is related to significant morbidity and mortality. In our country, there is no evaluation about CIED infection. Therefore, our aim was to investigate clinical characteristics and outcome of patients who had infection related to CIED implantation or replacement. The study included 144 consecutive patients with CIED infection treated at 11 major hospitals in Turkey from 2005 to 2014 retrospectively. We analyzed the medical files of all patients hospitalized with the diagnosis of CIED infection. Inclusion criteria were definite infection related to CIED implantation, replacement, or revision. Generator pocket infection, with or without bacteremia, was the most common clinical presentation, followed by CIED-related endocarditis. Coagulase-negative staphylococci and Staphylococcus aureus were the leading causative agents of CIED infection. Multivariate analysis showed that infective endocarditis and ejection fraction were the strongest predictors of in-hospital mortality.